Meteorosensitivity of patients with rheumatic musculoskeletal diseases - Ulrich A. Walker; Katja Nettermann; Sebastian Walker; Adam Streeter; Veronika K. Jaeger (PLoS ONE, 2025)
Objectives To evaluate if self-assessed rheumatic disease activity in patients with rheumatoid arthritis (RA), psoriatic arthritis (PsA) or ankylosing spondyloarthritis (AS) is linked to local weather. Methods In this prospective, multicentre study in Switzerland, adult patients were asked to report geographic location and rheumatic disease activity by means of Routine Assessment of Patient Index Data 3 (RAPID3)) via a webApp. The associations between RAPID3 scores and weather data on the day of the RAPID3 entry and the preceding week was investigated through regression analysis. Results 238 patients were included (61.3% female). 100 patients had RA (baseline mean DAS28-CRP 2.8), 47 patients had PsA, and 91 patients had AS (mean BASDAI 3.8). 45.0% of all patients declared themselves as meteorosensitive. In the entire cohort, we found a weak negative correlation (r = −0.167) between RAPID3 and air pressure, the correlations between the remaining weather variables were weak (r < 0.1). In the subgroups of meteorosensitive AS and PsA patients, we identified negative correlations between RAPID3 and air pressure (r = −0.321 and −0.232 respectively). In the AS meteorosensitive group, there was also weak correlation between wind and RAPID3 (r = 0.144). In RA patients, only negligible correlations (r < 0.1) were observed, regardless of meteorosensitivity. In all analyses, also in the analyses of weather changes over the preceding week, we failed to identify effect sizes that exceed the minimal clinically important difference of the RAPID3. Conclusions We did not find weather to be a major factor in disease activity of RA, AS and PsA patients receiving DMARD treatment.